2022
DOI: 10.3389/fpsyg.2022.835909
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Personality Traits in Two Types of Family Structure—A Cross-Sectional Study in China

Abstract: ObjectiveThe level of health literacy is one of the important factors affecting health outcomes. Family is an important place to shape personality traits, and people with different personalities will adopt different lifestyles, which will lead to variations in health outcomes. Therefore, this article aims to explore the relationship between health literacy and personality and its influencing factors in different family structures.MethodsThis was a cross-sectional study with 1,406 individuals. A questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
(87 reference statements)
0
10
0
1
Order By: Relevance
“…These sources can be useful in developing functional health literacy skills to the selection of products and services. Additionally, families shape personality traits, and people with different personalities will adopt different lifestyles, resulting in variations in health outcomes ( 36 ). Family engagement is critical to fostering positive health outcomes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…These sources can be useful in developing functional health literacy skills to the selection of products and services. Additionally, families shape personality traits, and people with different personalities will adopt different lifestyles, resulting in variations in health outcomes ( 36 ). Family engagement is critical to fostering positive health outcomes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, desirability respondents would have higher compliance and be more likely to practice emergency prevention measures such as preparing a first-aid kit as recommended by the government and other authorities. Personality traits may influence health literacy ( 56 ), Mai et al ( 57 ) explored the relationship between Big Five personality and health literacy and found that openness had the highest correlation with health literacy. In this study, the high openness group of Big Five personality was more willing to prepare a home first-aid kit than the group with a low degree of openness.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Cronbach's alpha of the short version of the health literacy scale was 0.940, and the Cronbach's alphas of the three subscales of health care, disease prevention, and health promotion were, respectively, 0.856, 0.860, and 0.868, all with good reliability. With reference to relevant literature, this study divided the respondents into two groups based on their health literacy: high group (above 33 points) and low group (33 points and below) ( 40 , 42 , 43 ).…”
Section: Methodsmentioning
confidence: 99%